General requirements for Home and Building Electronic Systems (HBES) and Building Automation and Control Systems (BACS). Smart grid. Application specification. Interface and framework for customer. Interface between the CEM and Home/Building Resource manager. General Requirements and Architecture Part 12-1, (2nd August 2018) - British Standards Institution,
No abstract available